Rotigotine Transdermal Patch for Motor and Non-motor Parkinson’s Disease: A Review of 12 Years’ Clinical Experience - Raeder, Vanessa (CNS Drugs, 2021)
Motor and non-motor symptoms (NMS) have a substantial effect on the health-related quality of life (QoL) of patients with Parkinson's disease (PD). Transdermal therapy has emerged as a time-tested practical treatment option, and the rotigotine patch has been used worldwide as an alternative to conventional oral treatment for PD. The efficacy of rotigotine on motor aspects of PD, as well as its safety and tolerability profile, are well-established, whereas its effects on a wide range of NMS have been described and studied but are not widely appreciated. In this review, we present our overall experience with rotigotine and its tolerability and make recommendations for its use in PD and restless legs syndrome, with a specific focus on NMS, underpinned by level 1–4 evidence. We believe that the effective use of the rotigotine transdermal patch can address motor symptoms and a wide range of NMS, improving health-related QoL for patients with PD. More specifically, the positive effects of rotigotine on non-motor fluctuations are also relevant. We also discuss the additional advantages of the transdermal application of rotigotine when oral therapy cannot be used, for instance in acute medical emergencies or nil-by-mouth or pre/post-surgical scenarios. We highlight evidence to support the use of rotigotine in selected cases (in addition to general use for motor benefit) in the context of personalised medicine.